Technical and forensic support of a defence counsel in criminal proceedings - V. O. Husieva; M. М. Kolomoitsev (Bulletin of Kharkiv National University of Internal Affairs)
The article determines that technical and forensic support of a defence counsel’s activities in criminal proceedings should be understood as a system of legal, organisational, scientific and technical provisions and applied measures for the development, implementation and practical use of technical means for the purpose of providing defence as intended, achieving the objectives of investigative ( search) and procedural actions, examination and recording of digital evidence. It is established that, as a general rule, current legislation does not prohibit the defence counsel from using technical and forensic means while participating in investigative (search) and procedural actions, at the same time, the defence counsel must notify all the participants of such an event of all the facts of their use, and the prosecution party, if there are objective grounds for this, although it may prohibit their use, but may do so only on the basis of a reasoned resolution, the investigating judge, the court – the ruling.